2004
DOI: 10.1080/13803390490509439
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the ApoE ε4 Allele on Recognition Memory for Olfactory and Visual Stimuli in Patients with Pathologically Confirmed Alzheimer’s Disease, Probable Alzheimer’s Disease, and Healthy Elderly Controls

Abstract: Episodic recognition memory for odors, faces, and unfamiliar symbols was assessed in apolipoprotein episilon4 positive and epsilon4 negative individuals with pathologically-confirmed Alzheimer's disease (AD), individuals diagnosed with probable AD, and healthy age- and gender-matched controls. The analyses revealed significant differences in performance between the AD patients and nondemented elderly controls based on the presence of the epsilon4 allele and the modality of the stimulus to be remembered. Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 0 publications
4
49
0
Order By: Relevance
“…Our results confirmed earlier findings showing that familiarity is similar across age groups (Gilbert & Murphy, 2004;Larsson & Bäckman, 1997). Both odor identification tasks showed a decrease in performance with age.…”
Section: Mean Frequenciessupporting
confidence: 95%
See 1 more Smart Citation
“…Our results confirmed earlier findings showing that familiarity is similar across age groups (Gilbert & Murphy, 2004;Larsson & Bäckman, 1997). Both odor identification tasks showed a decrease in performance with age.…”
Section: Mean Frequenciessupporting
confidence: 95%
“…The decline of cued odor identification performance often starts during the fifth (Doty et al, 1984a) and sixth decade of life (Brämerson, Johansson, Ek, Nordin, & Bende, 2004;Wehling, Espeseth, Reivang, Lundervold & Nordin, 2009). Findings are not consistent regarding familiarity: while Royet et al (2001) found that familiarity declined significantly with age, other authors have not confirmed this finding (Gilbert & Murphy, 2004;Larsson & Bäckman, 1997). Further studies of age effects in a sample performing different odor identification tasks are thus called for.…”
Section: Introductionmentioning
confidence: 83%
“…The data suggest that the possible protective effect of HT on olfaction may diminish in the later stages of the disease. This result corroborates with other recent studies investigating differences in olfactory-related tasks between ε4 positive and negative non-demented older adults and AD patient populations (Gilbert & Murphy, 2004;Murphy et al, 1998). Generally, these studies have only found differences between ε4 genotype in AD onset and severity of symptoms in the very early, preclinical stages of AD but these differences seem to wash out in the middle to later stages of AD.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, research studies have suggested that problems with remembering and detecting odors may be an early indication of cognitive impairment and dementing diseases in non-demented older adults (Devanand et al, 2002;Djordjevic et al, in press;Gilbert & Murphy, 2004b;Graves et al, 1999;Wang et al, 2002;Wilson et al, 2007). Although studies have examined odor learning in rats, it has not been clearly demonstrated whether odor learning is as affected by aging as visual learning in rats.…”
Section: Discussionmentioning
confidence: 99%